2011
DOI: 10.1159/000329508
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoglycans in the Normal and Pathological Breast Tissue of Humans: An Immunohistochemical and Molecular Study

Abstract: The sarcoglycan complex, consisting of α-, β-, γ-, δ- and ε-sarcoglycans, is a multimember transmembrane system providing a mechanosignaling connection from the cytoskeleton to the extracellular matrix. Whereas the expression of α- and γ-sarcoglycan is restricted to striated muscle, other sarcoglycans are widely expressed. Although many studies have investigated sarcoglycans in all muscle types, insufficient data are available on the distribution of the sarcoglycan complex in nonmuscle tissue. On this basis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 83 publications
2
21
0
Order By: Relevance
“…present in other non-muscular districts, e.g. breast epithelium [Arco et al, 2011] or respiratory, intestinal and urinary epithelium (data not shown). Therefore, it can be suggested that the SG complex is not muscle specific but rather ubiquitously present in several tissue regions in which, however, its role may differ depending on the different interactions.…”
Section: μMmentioning
confidence: 78%
See 1 more Smart Citation
“…present in other non-muscular districts, e.g. breast epithelium [Arco et al, 2011] or respiratory, intestinal and urinary epithelium (data not shown). Therefore, it can be suggested that the SG complex is not muscle specific but rather ubiquitously present in several tissue regions in which, however, its role may differ depending on the different interactions.…”
Section: μMmentioning
confidence: 78%
“…Cai et al [2007] studied SGC in Schwann cells and its role in the stability of peripheral nerve myelin. Studies on SGs are inconsistent: in some SGs were only noted in striated and smooth muscles, whereas other studies also showed their presence in non-muscle cells [Ettinger et al, 1997;Arco et al, 2011]. Recently, SGs have also been ascribed a role in CNS function and CNS disease [Zimprich et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Our data show the presence of all SGs in normal prostatic tissue, and as such are in contrast with previous reports which hypothesized that α‐ and γ‐SG are expressed in skeletal and cardiac muscle only (Roberds et al, ; Lim et al, ; Noguchi et al, ; Nigro et al, ; Liu et al, ), suggesting that the SGC is not muscle‐specific. Previously, our preliminary data on epithelial cells of many districts (unpublished data) and on epithelial cells of breast have shown that all SGs are clearly detectable, evidencing a wider distribution of the SGC (Arco et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…In the past, it was shown that mutations in any SG cause Limb-Girdle Muscular Dystrophy (Campbell, 1995) provoking, interestingly, dysphagia, vomiting and acute digestive dilatations (Barhon et al, 1998). In our opinion, to understand the real role and function of SGs, it is necessary to study these proteins, not only in normal, but also in pathological conditions, as we previously did, in breast epithelium (Arco et al, 2012). For this reason, we have analyzed all SGs also in human samples of prostatic glandular epithelium from patients affected by benign prostatic hyperplasia and prostatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Data about their role in cancer progression are scarce, consisting of a few reports on different types of cancer. Downregulation of SGCG was detected in NSCLC [49] and breast cancer [50], while Saraon et al [51] revealed elevation of PROS1 in high grade aggressive prostate cancer. Contrary to this, PROS1 seems to be downregulated in anaplastic meningiomas [52].…”
Section: Discussionmentioning
confidence: 98%